2013
DOI: 10.3323/jcorr.62.289
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Prestressing Steel in a Solution of 20% Ammonium Thiocyanate

Abstract: High-strength steels or PC steel products are used for pre-stressed concrete structures. Testing of PC steel products in terms of hydrogen embrittlement is specified in the FIP Report, and the test method adopted in ISO 15630 is well known. This test is called the FIP test, whereby a constant load is applied to PC steel in a 20 , 50 ammonium thiocyanate solution. An investigation was carried out on the corrosion behavior of 1,400 MPa class PC steel products in a FIP testing environment. Under this testing envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…A time to rupture of approximately 120 h is seen for the FIP test condition of a 20 mass% NH 4 SCN solution. The time to rupture did not change with the 15 mass% NH 4 SCN solution, but with a solution concentration of 10 mass% it increased by 30 h and with the 2 mass% solution it exceeded the test termination time of 200 h. The consumption of NH 4 SCN accompanying corrosion of the steel specimens in the 20 mass% NH 4 SCN solution at 50°C was estimated to be less than 2 mass% even after an elapsed time of 200 h. 6) This indicates that consumption of NH 4 SCN during hydrogen embrittlement testing has a negligible effect on the time to rupture. Figure 2 shows the effect of the NH 4 SCN solution concentration on the hydrogen content and weight loss of the steel specimens due to corrosion during the immersion tests.…”
Section: Potentiostatic Electrolysis Testsmentioning
confidence: 80%
See 4 more Smart Citations
“…A time to rupture of approximately 120 h is seen for the FIP test condition of a 20 mass% NH 4 SCN solution. The time to rupture did not change with the 15 mass% NH 4 SCN solution, but with a solution concentration of 10 mass% it increased by 30 h and with the 2 mass% solution it exceeded the test termination time of 200 h. The consumption of NH 4 SCN accompanying corrosion of the steel specimens in the 20 mass% NH 4 SCN solution at 50°C was estimated to be less than 2 mass% even after an elapsed time of 200 h. 6) This indicates that consumption of NH 4 SCN during hydrogen embrittlement testing has a negligible effect on the time to rupture. Figure 2 shows the effect of the NH 4 SCN solution concentration on the hydrogen content and weight loss of the steel specimens due to corrosion during the immersion tests.…”
Section: Potentiostatic Electrolysis Testsmentioning
confidence: 80%
“…Because all of the test specimens displayed a black color following the immersion tests, it was inferred that iron sulfides and iron oxides formed on the surface. 6) The authors previously reported that the corrosion rate in a pure oxygen atmosphere in a 24-h immersion test in a 20 mass% NH 4 SCN solution was approximately double the rate in a deaeration atmosphere, although the increase in the hydrogen content of the tested steel remained at about 5%. 5) These results indicated that, with a low NH 4 SCN solution concentration where a small quantity of hydrogen is absorbed, dissolved oxygen has a large effect on the corrosion rate of the steel, but the reduction reaction of dissolved oxygen has a small effect on hydrogen absorption.…”
Section: Potentiostatic Electrolysis Testsmentioning
confidence: 97%
See 3 more Smart Citations